Legal Implications Regarding Changes to The Foundation's Articles of Association according to Law Number 28 of 2004 - Yunus, Nur Rohim; Aji, Ahmad Mukri; Mukri, Syarifah Gustiawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
This study aims to analyze the legal implications of changes to the foundation's articles of association, based on the provisions of Law No. 28 of 2004, which amends Law No. 16 of 2001 concerning Foundations. This study employs a qualitative method with a normative legal approach, grounded in a comprehensive examination of laws and regulations, jurisprudence, and relevant scientific literature. The study's results indicate that changes to the foundation's articles of association have a direct impact on the legality of the foundation's organs, the validity of legal relations with third parties, and the potential for legal sanctions if the specified procedures are not followed. The provisions of Law Number 28 of 2004 emphasise the importance of an accountable and transparent organisational structure through a change mechanism that must be legally registered and approved. Failure to comply with this procedure can result in the cancellation of legal actions, the invalidity of deeds, and weaken the foundation's social function in society. Therefore, understanding and socialising the law to foundation administrators is an important step to prevent violations, while ensuring the sustainability of the foundation as a non-profit institution that serves the public interest.Keywords: Foundation; Articles of Association; Changes; Legal Implications; Law Number 28 of 2004